Effect of Oropharyngeal Administration of Colostrum in Premature Newborns ≤32 Weeks of Gestation on the Immune Response and Neonatal Morbidity: A Double-Blind Randomized Clinical Trial - Romero-Maldonado, Silvia; Soriano-Becerril, Diana Mercedes; García-May, Perla Karina; Reyes-Muñoz, Enrique; Muñoz-Ortíz, Eudoxia Georgina; Carrera-Muiños, Sandra; Granados-Cepeda, Martha Lucía; Cardona-Pérez, Jorge Arturo; Castro-Millán, Elsa; Segura-Cervantes, Enrique; Ceballos, Guillermo; Montoya-Estrada, Araceli (Frontiers in Pediatrics, 2022)
Introduction: The mother's colostrum carries immunological components such as cytokines and immunoglobulins derived from the maternal circulation with bacteriostatic properties. Objective: To evaluate the effect of oropharyngeal administration of colostrum (OPAC) versus placebo in the first four days of life in premature newborns 32 weeks of gestation on serum immunoglobulins concentration, neonatal morbidity and total days of hospitalization. Hypothesis: The OPAC increases serum immunoglobulins, decreases morbidity and total days of hospitalization. Material and Methods: A double-blind randomized controlled trial. Group 1: Placebo (P) (n = 50), Group 2: Colostrum (C) (n = 46). A blood sample was obtained at baseline, 7 and 28 days of life to quantify IgG, IgA, and IgM. Results: The C group showed an increase in serum IgA on day 28 expressed as median and [interquartile range]; C: 25 [12-35] vs. P: 11 [8-18], p <0.001. There were no significant differences on neonatal morbidity. Newborns in colostrum group showed completed the enteral feeding earlier (days) C: 13.9 ± 7 vs. P: 17.4 ± 8.4, p <0.04, they reached the birth weight earlier C: 10.9  2.8 vs. P: 12.9  4, p <0.01 and had less days of hospitalization C: 60.2 ± 33.8 vs. P: 77.2 ± 47.3, p <0.04. Neonatal mortality was lower in colostrum group than placebo group 0% versus 12%, respectively, without statistical difference (p=0.06). Conclusions: In premature newborns  32 weeks of gestation the OPAC within four days after birth increase serum IgA concentration at day 28 compared to placebo. Likewise, OPAC decrease the days to complete enteral feeding, reach the birth weight and total days of hospitalization.